The effect of silver and calcium fluoride nanoparticles on antibacterial activity of composite resin against Streptococcus mutans: An in vitro study - Mehdi Fathi; Zahra Hosseinali; Tina Molaei; Somayeh Hekmatfar (Dental Research Journal)
Background: Recurrent caries were attributed to the lack of antibacterial properties of the dental materials. Silver nanoparticles (AgNPs) and calcium fluoride nanoparticles (CaF2NPs) are broad-spectrum antibacterial agents. The object of the study was to investigate the antibacterial properties of composite-incorporated AgNPs and CaF2NPs on Streptococcus mutans. Materials and Methods: This experimental study forty-eight disks containing 0.5, 1, and 1.5% wt AgNPs s (n = 24) and 5, 10, and 15% wt CaF2NPs were prepared from flowable composite resin (n = 24). The third group consisted of 9 types of the combination of AgNPs and CaF2NPs (n = 72). A field emission scanning electron microscope with an energy-dispersive X-ray spectroscopy analysis system was used to test for the presence of nanoparticles in composite resins. The antibacterial efficacy of dental composite was evaluated by disk diffusion agar test. The minimum inhibitory concentration (MIC) and minimal bactericidal concentration were conducted. Data were analyzed using one-way ANOVA and multiple Tukey HSD (Honestly Significant Difference) tests. Significance level was set at 0.05. Results: Nanoparticles added to composite produce bacterial inhibition zone. The greatest inhibition of bacterial growth was recorded in the third group which contained both nanoparticles (P < 0.05). MIC values decreased after adding CaF2 NPs to the AgNPs-containing composite. The results of the FE-SEM test indicate the presence of AgNPs and CaF2NPs in the dental composite resin sample. On the other hand, the formation of AgNPs and their elemental nature were proved using energy dispersive X-ray microanalysis EDX analysis. According to the results, composite resins containing 0.5% of AgNPs s and 15% of CaF2NPs exhibited a significantly lower antibacterial activity compared to the 1.5% and 1% of AgNPs s with 15% of CaF2NPs (P < 0.05). Conclusion: Dental composite resins-containing CaF2NPs and AgNPs showed anti-bacterial activity against S. mutans.